Emerging Trends in Electrical, Electronic and Communications Engineering Proceedings of the First International Conference on Electrical, Electronic and Communications Engineering (ELECOM 2016), Bagatelle, Mauritius, November 25 -27, 2016 - Fleming, Peter; Vyas, Nalinaksh; Sanei, Saeid; Deb, Kalyanmoy (Lecture Notes in Electrical Engineering,, 2017)
The book reports on advanced theories and methods in two related engineering fields: electrical and electronic engineering, and communications engineering and computing. It highlights areas of global and growing importance, such as renewable energy, power systems, mobile communications, security and the Internet of Things (IoT). The contributions cover a number of current research issues, including smart grids, photovoltaic systems, wireless power transfer, signal processing, 4G and 5G technologies, IoT applications, mobile cloud computing and many more. Based on the proceedings of the first International Conference on Emerging Trends in Electrical, Electronic and Communications Engineering (ELECOM 2016), held in Voila Bagatelle, Mauritius from November 25 to 27, 2016, the book provides graduate students, researchers and professionals with a snapshot of the state-of-the-art and a source of new ideas for future research and collaborations.